Association between postoperative ibuprofen exposure and acute kidney injury after pediatric cardiac surgery - Sheng Shi; Chao Xiong; Dongyun Bie; Zhongrong Fang; Jianhui Wang (Renal Failure)
Background Acute kidney injury (AKI) is a common complication after pediatric cardiac surgery and is associated with worse outcomes. Ibuprofen is widely used in the perioperative period and can affect kidney function in children. However, the association between ibuprofen exposure and AKI after pediatric cardiac surgery has not been determined yet.Methods In this retrospective cohort study, children undergoing cardiac surgery with cardiopulmonary bypass were studied. Exposure was defined as given ibuprofen in the first 7 days after surgery. Postoperative AKI was diagnosed using the KDIGO criteria. A multivariable Cox regression model was used to assess the association between ibuprofen exposure and postoperative AKI by taking ibuprofen as a time-varying covariate.Results Among 1,112 included children, 198 of them (17.8%) experienced AKI. In total, 396 children (35.6%) were exposed to ibuprofen. AKI occurred less frequently among children who were administered ibuprofen than among those who were not (46 of 396 [11.6%] vs. 152 of 716 [21.2%], p < 0.001). Using the Cox regression model accounting for time-varying exposures, ibuprofen treatment was not associated with AKI (adjusted HR, 0.99; 95% CI 0.70–1.39, p = 0.932). This insignificant association was consistent across the sensitivity and subgroup analyses.Conclusions Postoperative ibuprofen exposure in pediatric patients undergoing cardiac surgery was not associated with an increased risk of AKI.